New scholarly pathways on green gentrification: What does the urban 'green turn' mean and where is it going?. (December 2019) - Anguelovski, Isabelle; Connolly, James JT; Garcia-Lamarca, Melissa; Cole, Helen; Pearsall, Hamil
Scholars in urban political ecology, urban geography, and planning have suggested that urban greening interventions can create elite enclaves of environmental privilege and green gentrification, and exclude lower-income and minority residents from their benefits. Yet, much remains to be understood in regard to the magnitude, scope, and manifestations of green gentrification and the forms of contestation and resistance articulated against it. In this paper, we propose new questions, theoretical approaches, and research design approaches to examine the socio-spatial dynamics and ramifications of green gentrification and parse out why, how, where, and when green gentrification takes place.